La consolidación y difusión de un mito fundacional: La Revolución de Mayo en los textos escolares, 1880-1905 - Poggi, Marta Mercedes (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2010)
The process of nation building of Argentina had as foundations two projects closely linked, one historiographical and other educational. Both projects build a new historical memory that had an important broadcaster in textbooks. These books acted as inventories of what was necessary to know about Argentina. History and memory offered a vital value to the May Revolution, and the educational system history texts contributed to the construction and broadcast of it as a foundational myth functional to the model of citizenship developed since 1880.